EXPLORING DEBT FINANCING OPTION FOR SME’S : A SYSTEMATIC LITERATURE REVIEW - Wardiman, Jery; Wardi, Yunia; Marwan, Marwan; Nofriansyah, Nofriansyah (Universitas Nusa Cendana, 2024)
The development and success of small and medium-sized enterprises (SMEs) are highly dependent on accessible and suitable financing options. This article provides an in-depth review of various SME financing sources, examining the benefits, drawbacks, and impacts of each option, including fintech lending, traditional bank financing, and venture capital. The findings offer a systematic understanding of SME finance dynamics. Results indicate that while venture capital can accelerate growth, it often raises challenges related to sustainability and governance. In contrast, bank financing provides stability but is hindered by high interest rates and complex bureaucratic processes. Fintech financing offers rapid access and ease but comes with heightened security and risk assessment concerns. The study suggests that SMEs should align funding choices with their unique needs and characteristics. Additionally, regulators and stakeholders are encouraged to increase their knowledge and safeguards in response to the expanding fintech lending market. Future research could explore innovative, eco-friendly financing solutions to meet SMEs' evolving needs. This article contributes valuable insights to stakeholders, supporting the sustainable growth of SMEs. Keywords: SME Financing; Debt Financing; Fintech Lending; Bank Financing; Venture Capital